XGANDALF – extended gradient descent algorithm for lattice finding. Issue 5 (30th August 2019) - Gevorkov, Yaroslav; Yefanov, Oleksandr; Barty, Anton; White, Thomas A.; Mariani, Valerio; Brehm, Wolfgang; Tolstikova, Aleksandra; Grigat, Rolf-Rainer; Chapman, Henry N.
Abstract : A description and evaluation are given of XGANDALF, extended gradient descent algorithm for lattice finding, an algorithm developed for fast and accurate indexing of snapshot diffraction patterns. Abstract : Serial crystallography records still diffraction patterns from single, randomly oriented crystals, then merges data from hundreds or thousands of them to form a complete data set. To process the data, the diffraction patterns must first be indexed, equivalent to determining the orientation of each crystal. A novel automatic indexing algorithm is presented, which in tests usually gives significantly higher indexing rates than alternative programs currently available for this task. The algorithm does not require prior knowledge of the lattice parameters but can make use of that information if provided, and also allows indexing of diffraction patterns generated by several crystals in the beam. Cases with a small number of Bragg spots per pattern appear to particularly benefit from the new approach. The algorithm has been implemented and optimized for fast execution, making it suitable for real‐time feedback during serial crystallography experiments. It is implemented in an open‐source C++ library and distributed under the LGPLv3 licence. An interface to it has been added to the CrystFEL software suite.